Perceptions And Experiences of Stakeholders on Effectiveness of the Psychiatric Nursing Training Program of the College of Nursing Mulleriyawa - Menike, W.A.R.P. (My University, 2021)
Introduction: The psychiatric nursing training program conducted in the College of Nursing Mulleriyawa (CNM) is the only training available in Psychiatry for the student nurses in Colleges of Nursing, Ministry of Health in Sri Lanka. There is no previous research study conducted to explore the effectiveness of this program. Objective: To explore the effectiveness of the psychiatric nursing training program conducted in CNM. Methods: Descriptive qualitative research was conducted using focus group (FG) discussions among nursing tutors of CNM (N=06), nursing officers and nurse managers (N=07) of the National Institute of Mental Health (NIMH). The participants with more than 05 years of experience in the field were included in the study using purposive sampling. A topic guide prepared using the CIPP model (Context, Input, Process, and Product) was used to collect data. Qualitative content analysis was used to analyze data. Ethical approval was obtained from the NIMH, Sri Lanka. Results: The study participants perceived the following concerns. The theme ‘Context’ -The program will be more effective if the revised curriculum includes the country's community needs and social changes. The theme ‘Input’ - Inadequacy of human and physical resources are the main barriers to the smooth process of the program to have effective outcomes. The theme ‘Process’-The program will be more effective if the duration of the program is extended. The theme ‘Product’ - The nursing students get a considerable change in their attitudes and skills for caring the Psychiatric patients due to this training. Conclusions: Stakeholders have perceived that the psychiatric training program at CNM is beneficial and effective for the nursing students in Sri Lanka for caring for psychiatric patients. The policymakers should initiate strategies to revise the curriculum and fulfil the physical and human resources to improve the program's effectiveness.

Introduction: The psychiatric nursing training program conducted in the College of Nursing Mulleriyawa (CNM) is the only training available in Psychiatry for the student nurses in Colleges of Nursing, Ministry of Health in Sri Lanka. There is no previous research study conducted to explore the effectiveness of this program. Objective: To explore the effectiveness of the psychiatric nursing training program conducted in CNM. Methods: Descriptive qualitative research was conducted using focus group (FG) discussions among nursing tutors of CNM (N=06), nursing officers and nurse managers (N=07) of the National Institute of Mental Health (NIMH). The participants with more than 05 years of experience in the field were included in the study using purposive sampling. A topic guide prepared using the CIPP model (Context, Input, Process, and Product) was used to collect data. Qualitative content analysis was used to analyze data. Ethical approval was obtained from the NIMH, Sri Lanka. Results: The study participants perceived the following concerns. The theme ‘Context’ -The program will be more effective if the revised curriculum includes the country's community needs and social changes. The theme ‘Input’ - Inadequacy of human and physical resources are the main barriers to the smooth process of the program to have effective outcomes. The theme ‘Process’-The program will be more effective if the duration of the program is extended. The theme ‘Product’ - The nursing students get a considerable change in their attitudes and skills for caring the Psychiatric patients due to this training. Conclusions: Stakeholders have perceived that the psychiatric training program at CNM is beneficial and effective for the nursing students in Sri Lanka for caring for psychiatric patients. The policymakers should initiate strategies to revise the curriculum and fulfil the physical and human resources to improve the program's effectiveness.
Keywords: Context; Curriculum; Input; Nursing; Evaluation